2021
DOI: 10.1021/acschembio.1c00810
|View full text |Cite
|
Sign up to set email alerts
|

Metabolically Activated Proteostasis Regulators Protect against Glutamate Toxicity by Activating NRF2

Abstract: The extracellular accumulation of glutamate is a pathologic hallmark of numerous neurodegenerative diseases including ischemic stroke and Alzheimer’s disease. At high extracellular concentrations, glutamate causes neuronal damage by promoting oxidative stress, which can lead to cellular death. This has led to significant interest in developing pharmacologic approaches to mitigate the oxidative toxicity caused by high levels of glutamate. Here, we show that the small molecule proteostasis regulator AA147 protec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…In the present study, the collagen peptide FLAP increased the activity of SOD, GSH-Px, and CAT in the liver and kidneys of mice, indicating that FLAP reduced oxidative damage in vivo by scavenging more free radicals. The Nrf2/ARE pathway is an important defense response system to oxidative stress. , Nrf2 can regulate the expression levels of antioxidant genes such as SOD, GSH-Px, and HO-1. This study showed that FLAP treatment significantly up-regulated the expression of Nrf2 in both the liver and kidneys, thereby increasing HO-1 levels by more than three times relative to the CCl 4 group.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the collagen peptide FLAP increased the activity of SOD, GSH-Px, and CAT in the liver and kidneys of mice, indicating that FLAP reduced oxidative damage in vivo by scavenging more free radicals. The Nrf2/ARE pathway is an important defense response system to oxidative stress. , Nrf2 can regulate the expression levels of antioxidant genes such as SOD, GSH-Px, and HO-1. This study showed that FLAP treatment significantly up-regulated the expression of Nrf2 in both the liver and kidneys, thereby increasing HO-1 levels by more than three times relative to the CCl 4 group.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, genes, such as ATF6 and the inositol-requiring enzyme 1 (IRE1)/X-box protein 1 (XBP1s), were activated via DESeq2 analysis of genes. Together, activation of Nrf2 in neurons by small protein homeostasis regulators involves selection of mechanisms for electrophilic and covalent modification of Keap1 (Rosarda et al, 2021).…”
Section: Modification Of Keap1 Cysteine Residues By Nrf2 Covalent Act...mentioning
confidence: 99%
“…For example, the small molecule AA147 is a proteostasis regulator that activates the 10.3389/fncel.2022.907560 ATF6 arm of the UPR, thereby reducing ER stress. In addition to this mechanism of action, AA147 also protects against glutamate-mediated excitotoxcity by activating nuclear factor erythroid 2-related factor 2 (NRF2) regulated oxidative stress response, and thus reduces oxidative damage to cells (Rosarda et al, 2021). While there is currently no direct evidence that NMDAR signaling results in the oxidative stress that this drug is capable of reducing, it raises an additional consideration for dual effects of future therapeutics.…”
Section: Clearance Of Unfolded Proteins Is An Indispensable Component...mentioning
confidence: 99%